Raised sputum extracellular DNA confers lung function impairment and poor symptom control in an exacerbation-susceptible phenotype of neutrophilic asthma - Abdo, Mustafa; Uddin, Mohib; Goldmann, Torsten; Marwitz, Sebastian; Bahmer, Thomas; Holz, Olaf; Kirsten, Anne-Marie; Trinkmann, Frederik; von Mutius, Erika; Kopp, Matthias; Hansen, Gesine; Rabe, Klaus F.; et al. (Respiratory research, 2021)
Extracellular DNA (e-DNA) and neutrophil extracellular traps (NETs) are linked to asthmatics airway inflammation. However, data demonstrating the characterization of airway inflammation associated with excessive e-DNA production and its impact on asthma outcomes are limited.